Tetra vs. octa-How it affects the photophysical, photochemical, physicochemical and biological properties of mercaptophenol-substituted Zn phthalocyanines - ŞAHİN, ZEYNEL (My University, 2022)
Zn phthalocyanines tetra- and octa- substituted in peripheral positions by mercaptophenol moieties were prepared. Photophysical, photochemical, physicochemical and biological properties relevant from a photodynamic therapy point of view have been determined, showing that the tetra-substituted derivatives have better potential, confirmed by in vitro tests performed on MCF-7 cells that induced significant cell death without showing dark toxicity.
Keywords: Kimya; Biyokimya; Alkoloidler; Temel Bilimler; Chemistry; Biochemistry; Alcaloides; Natural Sciences; KİMYA, MULTİDİSİPLİNER; Temel Bilimler (SCI); CHEMISTRY, MULTIDISCIPLINARY; CHEMISTRY; Natural Sciences (SCI); Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Chemistry (miscellaneous); General Chemistry; Physical Sciences; Phthalocyanine; mercaptophenol; singlet oxygen generation; photodynamic therapy; in vitro; PHOTODYNAMIC THERAPY; PERIPHERAL SUBSTITUTION; ZINC PHTHALOCYANINE; PHOTOSENSITIZERS